STUDIES ON HETEROGENEOUS HEMOLYTIC SERA - Kritchevsky, I. L. (The Rockefeller University Press, 1916)
Red corpuscles with nuclei contain heterogeneous sheep antigen when the organs of the same animal possess it. The sera in question contain not only heterogeneous hemolysins but also heterogeneous agglutinins. The hemolytic sera of rabbits immunized with hen red corpuscles are toxic to guinea pigs and kill them, the clinical picture being that of anaphylactic shock. Heterogeneous hemolysins are obtained by means of non-toxic antigen (hen red corpuscles injected into veins of rabbits). This fact refutes the theory of Friedberger, who attributed the antigenic power of a suspension of organs to its toxic character.